METHODOLOGICAL APPROACH TO CONSTRUCTION OF A SYSTEM FOR DETECTION AND PREVENTION OF DESTRUCTION OF THE ACTIVITIES OF CONSTRUCTION PARTICIPANTS - Mykhailo Malykhin; Denys Dubinin; Olha Bielienkova (Baltic Journal of Economic Studies)
The increasing complexity and risk exposure inherent in the implementation of construction projects underscores the critical need to develop a methodological framework aimed at detecting and preventing disruptive actions that threaten the performance of construction participants. The present study is dedicated to establishing a systematic approach to safeguard the activities of developers, contractors, and project stakeholders against destructive impacts, including reputational, financial, and operational disruptions. The objective of the research is to conceptualise and construct a preventive diagnostic system that integrates analytical models, digital monitoring platforms, and real-time communication protocols. The aim is to identify potential threats before they escalate into critical failures. The focal point of this study is the interaction environment of construction participants, wherein trust, information integrity, and process synchronization are identified as pivotal in ensuring project sustainability. The methodological foundation of the research combines system analysis, risk-oriented modelling, and process mapping techniques. The proposed framework incorporates the utilisation of behavioural indicators, deviation tracking algorithms, and early warning dashboards, which collectively facilitate proactive responses to disruption risks. Consequently, a modular architecture of a digital protection platform was developed, which facilitates real-time assessment of project vulnerabilities and supports adaptive decision-making across all stages of construction. The practical significance of this approach lies in its potential to reduce downtime, mitigate coordination failures, and enhance the reliability of project delivery. The results also offer valuable insights for improving communication transparency, automating compliance controls, and reinforcing institutional resilience within construction enterprises. The study makes a significant contribution to the development of intelligent support systems, which have the capacity to enhance the stability of construction actors in conditions of uncertainty, external shocks or deliberate interference.